New York State Curriculum, Mandated Tests and Congruence - New York State Education Dept., Albany; New York State Education Dept., Albany ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
This brochure is designed to acquaint persons involved in elementary and secondary instruction in New York State with State syllabi and the State testing program. The New York State testing program was mandated to measure student achievement and program effectiveness in the areas of mathematics, English language arts (reading and writing), science, social studies, and bilingual education. These areas constitute the core of the curriculum provided in elementary and secondary schools. While the use of the state syllabi in these core areas is recommended, rather than required, the content of required state tests are directly related to the goals and objectives of these syllabi. This fact makes it essential that administrators, supervisory personnel, and teachers be aware of the philosophy, the content, goals, and objectives of each syllabus and the nature of the testing program related to each core area. The student outcomes expected in language arts, mathematics, science, and social studies should also apply to limited English proficient students. Addresses are provided for each subject area from which further information can be obtained. (TJH)
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Achievement Tests; Bilingual Education Programs; Core Curriculum; Course Descriptions; Educational Assessment; Elementary School Curriculum; Elementary Secondary Education; English Curriculum; Mathematics Curriculum; Program Effectiveness; Reading Instruction; Science Curriculum; Secondary School Curriculum; Social Studies; State Programs; Testing Programs; Writing Instruction; New York; Mandated Tests; Reports, Evaluative